Gelling Characteristics and Mechanisms of Heat-Triggered Soy Protein Isolated Gels Incorporating Curdlan with Different Helical Conformations - Pei-Wen Long; Shi-Yong Liu; Yi-Xin Lin; Lin-Feng Mo; Yu Wu; Long-Qing Li; Le-Yi Pan; Ming-Yu Jin; Jing-Kun Yan (Foods)
This study investigated the effects of curdlan (CUR) with different helical conformations on the gelling behavior and mechanisms of heat-induced soy protein isolate (SPI) gels. The results demonstrated that CUR significantly improved the functional properties of SPI gels, including water-holding capacity (0.31–5.06% increase), gel strength (7.01–240.51% enhancement), textural properties, viscoelasticity, and thermal stability. The incorporation of CUR facilitated the unfolding and cross-linking of SPI molecules, leading to enhanced network formation. Notably, SPI composite gels containing CUR with an ordered triple-helix bundled structure exhibited superior gelling performance compared to other helical conformations, characterized by a more compact and uniform microstructure. This improvement was attributed to stronger hydrogen bonding interactions between the triple-helix CUR and SPI molecules. Furthermore, the entanglement of triple-helix CUR with SPI promoted the formation of a denser and more homogeneous interpenetrating polymer network. These findings indicate that triple-helix CUR is highly effective in optimizing the gelling characteristics of heat-induced SPI gels. This study provides new insights into the structure–function relationship of CUR in SPI-based gel systems, offering potential strategies for designing high-performance protein–polysaccharide composite gels. The findings establish a theoretical foundation for applications in the food industry.